Ultrafast Charge Transfer 2D MoS2/Organic Heterojunction for Sensitive Photodetector. Issue 12 (19th February 2023) - Xu, Zhuhua; He, Miao; Wu, Qinke; Wu, Chengcheng; Li, Xubiao; Liu, Bilu; Tang, Man‐Chung; Yao, Jie; Wei, Guodan
Abstract: The 2D MoS2 with superior optoelectronic properties such as high charge mobility and broadband photoresponse has attracted broad research interests in photodetectors (PD). However, due to the atomic thin layer of 2D MoS2, its pure photodetectors usually suffer from inevitable drawbacks such as large dark current, and intrinsically slow response time. Herein, a new organic material BTP‐4F with high mobility is successfully stacked with 2D MoS2 film to form an integrated 2D MoS2 /organic P–N heterojunction, facilitating efficient charge transfer as well as significantly suppressed dark current. As a result, the as‐obtained 2D MoS2 /organic (PD) has exhibited excellent response and fast response time of 332/274 µs. The analysis validated photogenerated electron transition from this monolayer MoS2 to subsequent BTP‐4F film, whereas the transited electron is originated from the A − exciton of 2D MoS2 by temperature‐dependent photoluminescent analysis. The ultrafast charge transfer time of ≈0.24 ps measured by time‐resolved transient absorption spectrum is beneficial for efficient electron–hole pair separation, greatly contributing to the obtained fast photoresponse time of 332/274 µs. This work can open a promising window to acquire low‐cost and high‐speed (PD). Abstract : The novel organic material BTP‐4F is stacked with monolayer MoS2 to form a heterojunction, facilitating efficient charge transfer as well as significantly suppressed dark current for the photodetector, which exhibits excellent responsivity of 3.2 A W −1, detectivity of 1.6 × 10 9 Jones, high external quantum efficiency of 756%, and fast response time of 332/274 µs.